War Trauma and Psychosocial Program in Croatia - Knezović, Zvonimir; Kocijan-Hercigonja, Dubravka (1996)
In the paper the Croatian psychosocial program for victims of war developed by the Government Office for Victims of War is presented.
Projekt MZOS
ENG